Implementation Of Compliance Assessment Of Public Service Provision By The Ombudsman In Improving Service Quality At The Dukcapil Service Of Bengkulu City: Implementasi Penilaian Kepatuhan Penyelenggaraan Pelayanan Publik Oleh Ombudsman Dalam Peningkatan Kualitas Pelayanan Di Dinas Dukcapil Kota Bengkulu - Mustari Tasti; Rahiman Dani; Alexsander Alexsander (Gayaku Publisher, 2026)
Optimal public service is the essence of good governance. However, various challenges such as low transparency, procedural uncertainty, and the potential for maladministration are still frequently encountered in bureaucratic practices in Indonesia. This study aims to analyze in-depth how the implementation of the public service compliance assessment by the Ombudsman of the Republic of Indonesia impacts the improvement of service quality at the Department of Population and Civil Registration (Disdukcapil) of Bengkulu City. This research adopts a qualitative approach with a descriptive method. Data collection was carried out through in-depth interviews, participant observation, and documentation studies involving internal Disdukcapil officials (Head of Department, Head of Division, Head of Administration, Receptionist) and five community service users. Data analysis is based on the Van Meter and Van Horn policy implementation model. The results showed that the Ombudsman's compliance assessment had a significant positive impact on improving service quality. From the aspect of policy objectives, there is an explicit increase in transparency regarding service standards, time certainty, and clarity of administrative costs. Interviews with service users unanimously confirmed the absence of illegal levies and the high level of hospitality of service officers. The success of this implementation is fully supported by the commitment of agency leaders, the absence of internal resistance to change, and strategic support from the Mayor and the Regional House of Representatives (DPRD) of Bengkulu City. Nevertheless, efforts to improve services are still faced with technical and structural obstacles, particularly related to information technology infrastructure, such as unstable WiFi networks and outdated server hardware, as well as the lack of specific budget allocations to follow up on the Ombudsman's recommendations. In conclusion, external supervision by the Ombudsman has not merely served as an administrative control instrument for fulfilling standards but has transformed into a catalyst for a more responsive and accountable organizational culture change at the Bengkulu City Disdukcapil.